Pemberdayaan Guru-Guru Bahasa Inggris SMP Kota Banjarmasin dalam Mengembangkan Soal Berbasis HOTS untuk Mengukur Kemampuan Membaca - Jumariati Jumariati; Noor Eka Chandra; Eka Puteri Elyani; Saarah Nabiilah Octaviani; Tsaltsa Rafiah Purnomo (Universitas Muhammadiyah Surakarta, 2022)
Having the ability to think critically is very important, especially for school-age teenagers who are still in the process of self-discovery and have not been able to sort out information. Teacher is an important figure in preparing students with critical thinking skills since teachers have a great opportunity to instill positive things that support the development of their students. That is why, it is important for teachers to be able to train their students to think critically and develop instruments that can measure students’ critical thinking skills. This activity aims to train teachers in developing instruments of critical thinking skills assessment in reading English texts. The method used is a participatory method in which emphasizing active participation of 35 teachers of English MGMP SMP in Banjarmasin. The implementation of this activity consists of delivering the material, evaluating the understanding of the material, assisting the compilation of questions, and analyzing question items. The findings show that 96% of the items compiled have met the standards of critical thinking assessment in the field of reading skills. In addition, more than 65% of the total items are formulated correctly according to the concept of assessment. This means that this activity has reached the target which 71% of the total participants scored more than equal to 6. It is concluded that the participants of the training have a good understanding of the concept of critical thinking assessment and are able to compile multiple choice questions based on critical thinking skills.